2024
DOI: 10.1101/2024.03.25.586532
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A network of interacting ciliary tip proteins with opposing activities imparts slow and processive microtubule growth

Harriet A. J. Saunders,
Cyntha M. van den Berg,
Robin Hoogebeen
et al.

Abstract: Cilia are essential motile or sensory organelles found on many eukaryotic cells. Their formation and function rely on axonemal microtubules, which exhibit very slow dynamics, however the underlying biochemical mechanisms are largely unexplored. Here, we reconstituted in vitro the individual and collective activities of the ciliary tip module proteins, CEP104, CSPP1, TOGARAM1, ARMC9 and CCDC66, which interact with each other and with microtubules, and, when mutated, cause ciliopathies such as Joubert syndrome. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 73 publications
(180 reference statements)
0
4
0
Order By: Relevance
“…To directly examine the role of CCDC66 in microtubule stabilization, we performed in vitro experiments using MBP-mNeonGreen-CCDC66, which was expressed and purified from insect cells as described previously [40]. MBP-mNeonGreen, which does not bind to microtubules, and the first two TOG domains of TOGARAM1, which bind free tubulin but not the microtubule lattice and promote microtubule polymerization but not stability in vitro , were used as controls [50, 57]. We polymerized rhodamine-labeled microtubules from 2 µM tubulin mixture in the presence of GTP and glycerol at 37°C for 30Lmin.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…To directly examine the role of CCDC66 in microtubule stabilization, we performed in vitro experiments using MBP-mNeonGreen-CCDC66, which was expressed and purified from insect cells as described previously [40]. MBP-mNeonGreen, which does not bind to microtubules, and the first two TOG domains of TOGARAM1, which bind free tubulin but not the microtubule lattice and promote microtubule polymerization but not stability in vitro , were used as controls [50, 57]. We polymerized rhodamine-labeled microtubules from 2 µM tubulin mixture in the presence of GTP and glycerol at 37°C for 30Lmin.…”
Section: Resultsmentioning
confidence: 99%
“…CSPP1, a component of the ciliary tip module, was shown to inhibit microtubule growth and shortening, as well as stabilize damaged microtubule lattices [77]. A recent study showed that CCDC66, along with CEP104, CSPP1, TOGAGRAM1 and ARMC9, forms a complex at the ciliary tip which stabilizes microtubules by promoting slow and processive growth of the microtubule plus ends [50]. This study also found that CCDC66 does not affect the frequencies of catastrophes and rescues, nor did it induce pausing, suggesting that CCDC66 acts as a scaffold for the recruitment of the axonemal tip MAPs involved in regulating microtubule dynamics [50].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations